1999
DOI: 10.1002/(sici)1098-2264(199907)25:3<205::aid-gcc2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imbalances of 7p and 17q in malignant peripheral nerve sheath tumors are clinically relevant

Abstract: We investigated 31 malignant peripheral nerve sheath tumors (MPNSTs) from 23 patients by means of comparative genomic hybridization (CGH) in order to study quantitative genomic aberrations of these tumors. Twenty‐one of the 23 patients revealed changes, with a mean value of 11 aberrations per sample (range 2–29). The minimal common regions of the most frequent gains were 8q23‐q24.1 (12 cases), 5p14 (11 cases), and 6p22‐pter, 7p15‐p21, 7q32‐q35, 8q21.1‐q22, 8q24.2‐qter, and 17q22‐qter (10 cases each). Seventeen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 4 publications
7
56
0
Order By: Relevance
“…Moreover, in 2 pleomorphic and in 4 dedifferentiated LS high level amplifications were detected within this subregion that harbors with MYB at 6q23.3-q24 a potential candidate oncogene. Frequent gains of 6q23-q24 including some amplicons were also identified in leiomyosarcomas 27,28 and malignant peripheral nerve sheath tumors 29,30 while being generally absent in well-differentiated LS/ALT. [23][24][25][26] Overrepresentations of chromosomal subregion 12q24 were likewise detected in about half of both the pleomorphic and the dedifferentiated LS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, in 2 pleomorphic and in 4 dedifferentiated LS high level amplifications were detected within this subregion that harbors with MYB at 6q23.3-q24 a potential candidate oncogene. Frequent gains of 6q23-q24 including some amplicons were also identified in leiomyosarcomas 27,28 and malignant peripheral nerve sheath tumors 29,30 while being generally absent in well-differentiated LS/ALT. [23][24][25][26] Overrepresentations of chromosomal subregion 12q24 were likewise detected in about half of both the pleomorphic and the dedifferentiated LS.…”
Section: Discussionmentioning
confidence: 94%
“…[23][24][25][26] Overrepresentations of chromosomal subregion 12q24 were likewise detected in about half of both the pleomorphic and the dedifferentiated LS. Gains of 12q24 have also been observed frequently in malignant peripheral nerve sheath tumors 29,30 while being mostly absent in well-differentiated LS/ALT. [23][24][25][26] Therefore, overrepresentations of 12q24 seem to be associated with tumor progression in lipogenic sarcomas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15 Chromosomal regions with a green to red ratio above 1.25 were considered to be overrepresented (gains), whereas regions with a ratio below 0.75 were considered to be under-represented (losses). The cutoff value for high-level amplifications was 1.5 according to Kallioniemi et al 14 The results were confirmed by calculating the double standard deviation of the individual ratio profiles for each chromosome within the same experiment.…”
Section: Analysis Of Digital Images Resulting From Cghmentioning
confidence: 99%
“…CGH was performed as described by Kallioniemi et al 14 but with some previously reported modifications. 15 Briefly, tumor DNA was labeled with biotin-16-dUTP, and reference DNA was labeled with digoxigenin-11-dUTP (Boehringer Mannheim, Mannheim, Germany) by using nick translation. Hybridization was performed for 3 days at 371C.…”
Section: Cgh Analysismentioning
confidence: 99%